Germline Polymorphisms and Length of Survival of Nasopharyngeal Carcinoma: An Exome‐Wide Association Study in Multiple Cohorts. Issue 10 (20th March 2020) - Guo, Yun‐Miao; Chen, Jie‐Rong; Feng, Yan‐Chun; Chua, Melvin L. K.; Zeng, Yanni; Hui, Edwin Pun; Chan, Allen K. C.; Tang, Lin‐Quan; Wang, Lin; Cui, Qian; Han, Hui‐Qiong; Luo, Chun‐Ling; et al.
Abstract: Germline polymorphisms are linked with differential survival outcomes in cancers but are not well studied in nasopharyngeal carcinoma (NPC). Here, a two‐phase association study is conducted to discover germline polymorphisms that are associated with the prognosis of NPC. The discovery phase includes two consecutive hospital cohorts of patients with NPC from Southern China. Exome‐wide genotypes at 246 173 single nucleotide polymorphisms (SNPs) are determined, followed by survival analysis for each SNP under Cox proportional hazard regression model. Candidate SNP is replicated in another two independent cohorts from Southern China and Singapore. Meta‐analysis of all samples ( n = 5553) confirms that the presence of rs1131636‐T, located in the 3′‐UTR of RPA1, confers an inferior overall survival (HR = 1.33, 95% CI = 1.20–1.47, P = 6.31 × 10 −8 ). Bioinformatics and biological assays show that rs1131636 has regulatory effects on upstream RPA1 . Functional studies further demonstrate that RPA1 promotes the growth, invasion, migration, and radioresistance of NPC cells. Additionally, miR‐1253 is identified as a suppressor for RPA1 expression, likely through regulation of its binding affinity to rs1131636 locus. Collectively, these findings provide a promising biomarker aiding in stratifying patients with poor survival, as well as a potential drug target for NPC. Abstract : This study reveals a functional germline polymorphism at RPA1 to be associated with survival outcome of patients with nasopharyngeal carcinoma (NPC). The study also shows that RPA1 is able to regulate tumor progression and radioresistance in NPC cells. Together, the study proposes the genetic variation of RPA1 as a promising germline biomarker for precise treatment planning and prognosis of NPC.